Optimization of Energy and Nitrogen Availability for Microbial Protein Synthesis and Growth Performance of Crossbred Calves - Ayyappan, K.; Singh, B.; Singhal, K.K. (Indian Journal of Animal Nutrition, 2018)
A study was conducted to assess the effect of dietary synchrony of energy and nitrogen (N) release in rumen on microbial protein synthesis and growth performance in crossbred calves. Two isonitrogenous and isocaloric diets were formulated on the basis of hourly OM and N degradation of each ingredient and the synchrony index (SI) of synchronous (S, SI 0.82) and asynchronous (AS, SI 0.57) diets were evaluated for microbial protein synthesis in vitro. The values of total gas and methane production were higher (P<0.01) while that of NH3-N was lower in S diets than in AS diets. Total N, TCA-ppt N, purine N, microbial N (MN), TVFA concentration and acetate to propionate ratio were higher (P<0.01) in S diets than in AS diets. In a 120 days feeding trial, 12 crossbred calves (BW= 100.61Â±4.54 kg, age= 7-8 months) were randomly divided into two groups and fed on total mixed diets varying in SI. Voluntary feed intake and nutrient digestibility were similar in both groups. N intake was higher (P<0.01) in calves fed on AS diet than on S diet. However, N retention, total purine absorption, MN flow to intestine and urinary excretion of purine derivatives were similar in the two groups. The efficiency of microbial protein synthesis in S and AS group was 23.49 and 23.26 g MN/kg DOMR, respectively and variation between groups was not significant. Hence, there was no difference in feed intake, digestibility of nutrients, body weight gain, feed efficiency, N balance and microbial protein synthesis in the growing calves fed either synchronous or asynchronous diets.